APPEAL PROCEDURE OF FISCAL ADMINISTRATIVE ACTS. THE MANDATORY PRELIMINARY APPEAL PROCEDURE - CÎRMACIU, Diana (International Journal of Legal and Social Order, 2022)
In a period in which are being organized more and more often control campaigns of the National Agency for Fiscal Administration (A.N.A.F.), with the aim of improving voluntary compliance and achieving the specific objectives of the agency, that of preventing and combating fraud and tax evasion, we believe that emphasis must be also placed on the rights of the taxpayer to ensure a balance between the general interest and the legitimate expectations of the individual, in a relationship based on good faith and compliance with the law. Contemporary reality proves us that even in this field we are still facing some “disorder” inherited or perpetuated from the complex of circumstances and difficulties through which the set of institutions and bodies with duties of carrying out the financial and fiscal policy of the state went through (thus including, here, and similar dispute resolution structures).